Primary and secondary caregiver depressive symptoms and family functioning following a pediatric cancer diagnosis: an exploration of the buffering hypothesis. Issue 6 (22nd March 2021) - Keim, Madelaine C.; Fladeboe, Kaitlyn; Galtieri, Liana R.; Kawamura, Joy; King, Kevin; Friedman, Debra; Compas, Bruce; Breiger, David; Lengua, Liliana; Katz, Lynn Fainsilber
Abstract: Objective: After diagnosis, caregivers of children with cancer, particularly mothers or primary caregivers (PCs), often show elevated depressive symptoms which may negatively impact family functioning. We tested PC and secondary caregiver (SC) depressive symptoms as predictors of family, co‐parenting, and marital functioning and whether having a non‐depressed SC buffers against potential negative effects of PC depressive symptoms. Methods: Families ( N  = 137) were recruited from two major children's hospitals following a diagnosis of pediatric cancer. Caregivers completed self‐report measures of depressive symptoms (Center for Epidemiological Studies‐Depression Scale; Depression, Anxiety, and Stress Scale) and marital functioning (Dyadic Adjustment Scale) at 1‐month post‐diagnosis. A subset of families ( n  = 75) completed videotaped interaction tasks at approximately 3‐months post‐diagnosis that were coded for family and co‐parenting interactions. Results: Higher PC depressive symptoms at 1‐month post‐diagnosis was associated with higher adaptability and lower conflict in family functioning. PC depressive symptoms were also associated lower dyadic consensus and lower dyadic satisfaction. SC depressive symptoms were not significantly associated with any family/co‐parenting/marital functioning variables. Significant interaction analyses suggested that SC depressive symptoms moderated the effect of PC depressive symptoms on family cohesion, withdrawn parenting, and affective expression in the marriage, such that the relationship between PC depressive symptoms and poorer functioning was attenuated when SC depressive symptoms were at low or average levels. Conclusions: Having a nondepressed SC buffered against negative effects of PC depressive symptoms on certain domains of family, coparenting, and marital functioning. SCs may play a protective role for families of children with cancer.